Lo ps. Acrone, Alcesti e sant’Agileo - PAOLUCCI, Paola (AL. Rivista di studi di Anthologia Latina, 2013)
Abstract Starting from the investigation of the Vergilian hemistics reused in the Cento Alcesta, the paper shows that a lot of those hemistics are reused with a semantic value, that involves the exegesis of Horatius by ps. Acro. The confirmation about the circulation of the ps. Acro’s Commentary in the Carthaginian milieu (that’s the same milieu of the Cento) comes from an apparently banal mistake in a ps. Acro’s annotation.